A Survey of Heat Dissipation in Rural vilage Housing of Cold Mountainous Climat - Tabesb, Shaghayegh (International Journal of Psychosocial Rehabilitation, 2020)
Due to the economic, social, cultural changes and the introduction of housing technology in Iran in the last few decades, there have been considerable changes in the housing architecture of mountainous village as one of the villages of mountainous cities. Also, these changes have transformed the image of village and increased the energy consumption in this village. Thus, by recognizing the vernacular architecture of villages to prevent heat loss through materials, we can help to improve the heat loss in the modern buildings of villages. Therefore, in order to achieve this goal, using quantitative case study and deductive method, the present study investigated the materials used in the wall and ceiling with window to floor ratio to achieve heat dissipation rate in 2 samples of vernacular housing and two samples of modern housing. Finally, the results of the study show that unlike the new buildings of the villages, the materials and architectures of vernacular housing in mountainous village have reduced the thermal dissipation by 20% due to the optimal use of climatic factors and vernacular materials (namely dried mud and wood).